Perancangan Aplikasi Laporan Pegawai Healt, Safety And Environment Pada PT IWIP Weda By Industrial Park - Andi Bulaeng; Sakinah, Nur; Tri Bata Biru Saputri (Politeknik Negeri FakFak, 2025)
This research focuses on creating the employees’ performance reporting application of Health, Safety, and Environment (HSE) of PT. IWIP Weda. The main aim of this development system is to optimize the making of the HSE employees' daily report. The Waterfall development method was chosen as the methodological approach in designing and implementing this application. The application is build based on web with PHP programming and MYSQL. Through this application the super admin is able to arrange the employees’ work report. Along with that, the frontman is able to dig out the occupational health violations in real time. Futhermore, this application loads the information of Occupational Safety and Health (K3). This web application is dessigned to be accessed online. Thus, the user is able to access information anytime and anywhere. In the final analysis, this application is able to simplify the reporting process, defining the HSE perfomance, discovering the occupational health violations, and storaging the data efficiently. The black-box testing shows that the system functions can run well. Moreover, application system has met the needs and showing good results. Based on the User Acceptance testing (UAT), the average value is 86%.